(untitled) (Pain medicine, 2016)
The article presents the pharmacological aspects of paracetamol usage in the context of current clinical guidelines. Attention is focused on pharmacokinetics studies, efficacy and safety of the drug in the treatment of pain and fever in adults and children. We analyzed possible ways and conditions of paracetamol biotransformation in the liver by microsomal oxidative system, which plays an important role in the development of adverse drug reactions. The review presents examples of drug pharmacological interactions with paracetamol, leading to hepatotoxic reactions. Some symptoms of intoxication with paracetamol, and the factors contributing to its development are given in the article. Detailed schemes of acetylcysteine antidote therapy for poisoning by paracetamol are also presented.